2015
DOI: 10.1093/infdis/jiv144
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and Geographic Relationships of Severe Fever With Thrombocytopenia Syndrome Virus in China, South Korea, and Japan

Abstract: Two clades of SFTSV may have evolved separately over time. On rare occasions, the viruses were transmitted overseas to the region in which viruses of the other clade were prevalent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
98
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(116 citation statements)
references
References 22 publications
10
98
0
4
Order By: Relevance
“…However, it is unclear whether the subclones existed in the original patient material or appeared through passages in Vero E6 cells. Yoshikawa et al reported the nucleotide sequences of the YG1 virus isolated from Vero cells and registered them in the DNA database of Japan (DDBJ) (19). These submitted sequences are identical to those of E3.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unclear whether the subclones existed in the original patient material or appeared through passages in Vero E6 cells. Yoshikawa et al reported the nucleotide sequences of the YG1 virus isolated from Vero cells and registered them in the DNA database of Japan (DDBJ) (19). These submitted sequences are identical to those of E3.…”
Section: Discussionmentioning
confidence: 99%
“…To date, all known HYSVs identified in China can be classified into six lineages [14,16,18] and there are three lineages of HYSVs in Japan [19 ] with the third lineage from Japan closely related to the HYSVs from Zhejiang Province, China. These data suggest that these viruses have a recent common ancestor, likely due to migration of their hosts.…”
Section: Genetic Characteristic Of Hysvmentioning
confidence: 99%
“…In Japan, 163 patients with SFTS were identified between the autumn of 2012 and October 2015, with most cases occurring in the western part of Japan, including Shimane Prefecture, located in Chugoku region of Honshu island (7)(8)(9).…”
Section: Communicated By Masayuki Saijomentioning
confidence: 99%